Topiramate as an adjunctive therapy in children with intractable epilepsy - Hardiono D. Pusponegoro; Tri Lestari Handayani; Irawan Mangunatmadja; Dwi Putro Widodo; Rulina Suradi (Paediatrica Indonesiana, 2002)
Background Epilepsy is a chronic disease that requires antiepileptic drugs (AEDs). Only 60-70% of new patients could be controlled effectively by standard AEDs and this stimulates the search for new, more effective and well-tolerated AEDs.Objective To asses the efficacy and safety of topiramate, as an adjunctive therapy to standard AEDs for children with intractable epilepsy.Methods This was an open label, parallel group study. Forty children with at least 4 seizures during a 4-week baseline period were randomly assigned to topiramate (n=20) or control group (n=20). In the topiramate group, the drug was given in adjunct to AEDs forÂ  2-week titration dosage continued with a 12-week stabilization period, while the control group received only AEDs adjusted to their clinical responses.Results Mean reduction from baseline in monthly seizures frequency was significantly greater in the topiramate group (88.6% vs. 25%; P=0.030). Other variable of efficacy was significantly different (e"50% reduction in seizures: 14/20 vs. 6 /20; P=0.049). Adverse effects of topiramate, such as decreased weight, paresthesia, somnolence, diarrhea, fever, aggressive reaction and flushing, were temporary and mild.Conclusion Results of this trial strongly suggested that topiramate is effective and well tolerated in reducing seizures of intractable epilepsy.